Difficulties of Elementary School Students in Solving Line and Angle Material Problems Using a Protractor - Galuh Nur Insani; Haldini Reygita; Mutia Ade Syafitri; Deti Rostika (CV. Rayyan Dwi Bharata, 2023)
Mathematics is a structured science which includes the basics of calculating, measuring, and depicting the shape of learning objects. Mathematics itself has a uniqueness that makes it different from learning in general. Information was obtained that students had difficulty learning geometry on things that were more conceptual in nature. The purpose of this study was to be able to find out the extent to which students' ability to solve problems measuring lines and angles using a protractor. This study used a type of qualitative research method in which the researcher made observations and collected data at one of the elementary schools in the Panyileukan area. Based on the research conducted, it can be seen that there are still many students who have difficulty working on problems measuring lines and angles using a protractor in mathematics.